The Total Landed Cost Concept. Begging for Answers - Andreas Pumpe; Franz Vallée (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
The Total Landed Cost (TLC) often comprise a large share of the total international sourcing cost and thereby determine the cost-saving potential. Therefore, the TLC must become an integral part when making international supplier selection decisions to be able to make deliberate choices on a case-by-base base. The literature proposes a number of frameworks to evaluate the TLC, but the ordinary way has not been examined satisfactorily. In this research, an online survey was conducted and the importance-performance analysis (IPA) was applied. IPA is an effective tool that simultaneously analyses quality attributes of the two dimensions performance and importance to identify areas needing improvement as well as areas of effective performance. The sample included 264 valid and usable respondents. As a result, reasons for an overall performance in need of improvement are the accessibility of required information and the duration of the TLC evaluation process. Based on a comprehensive literature review, this is probably why TLC frameworks with sufficient detail to prompt effective decision-making are not present in research. The authors discuss the resulting, derived research needs to enable an appropriate TLC evaluation in international supplier selection decisions.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Total Landed Cost; International Sourcing; Supplier Selection; Importance-performance Analysis